Automatic technical documentation of lithic artefacts by digital techniques. (December 2018) - Barone, S.; Neri, P.; Paoli, A.; Razionale, A.V.
Abstract: Despite the existence of a wide variety of standards to create hand-made illustrations of lithic artefacts, the conventional process is laborious, time-consuming and the quality of the drawings is highly variable. In this paper, a novel computer-based methodology to create automatic technical documentation of lithic artefacts, in the form of manual-like drawings, is presented. The method exploits the artefact digital model obtained by a 3D optical scanner. An optimization process is proposed to orient the digital model reproducing the conventional positioning. A lighting model is used to introduce an illumination source having different directions, to highlight surface details. A set of images is then created and segmented to retrieve the artefact outline and the internal ridges between flake scars. Potentialities of the proposed methodology are illustrated by analyzing three different stone artefacts acquired by a structured light scanner. 2D technological drawings are automatically created and compared to those obtained by an experienced lithic illustrator. Graphical abstract: Highlights: A computer-based method to create automatic drawings of lithic artefacts is presented. The method exploits the artefact 3D digital model obtained by an optical scanner. An illumination model is used to highlight surface details. Image sets are created and processed to obtain 2D illustrations of lithic artefacts. Comparisons between computer-based and manual-based illustrations are discussed.